Total Synthesis of Sulfated Glycosphingolipid SM1a, a Kind of Human Epithelial Carcinoma Antigen. Issue 3 (9th December 2014) - Zhang, Pengtao; Wang, Kun; Zhang, Jun; Li, Chunxia; Guan, Huashi
Abstract: A highly efficient and practical total synthesis of the sulfated ganglioside SM1a, a kind of human epithelial carcinoma antigen identified in mammalian kidney, has been accomplished for the first time. The characteristic sequence of SM1a, β‐D ‐Gal p ‐(1→3)‐β‐D ‐NHAcGal p ‐(1→4)‐β‐D ‐(3‐ O ‐sulfate)‐Gal p ‐(1→4)‐β‐D ‐Glc p ‐ceramide was assembled by a [3+2] convergent approach. A key trisaccharide building block was formed from a new galactose acceptor7 containing a potential sulfated site, GalNHTroc donor6, and galactose donor4 . The cyclic glucosyl ceramide was glycosylated with trisaccharide trichloroacetimidate2 to give the protected ganglioside backbone in good yield. Selective sulfonation at the 3‐OH of the Gal residue followed by global deprotection gave the target molecule SM1a. Abstract : An endogenous sulfoglycolipid from mammalian kidney, SM1a, has been synthesized. A [3+2] convergent approach to the target molecule was used. Coupling of the trisaccharide containing a potential sulfation site with a cyclic glucosyl ceramide (GlcCer) unit gave the backbone structure of SM1a, which was converted into ganglioside SM1a after selective sulfonation and global deprotection.